2007
DOI: 10.1111/j.1574-6941.2006.00268.x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance patterns in Enterobacteriaceae isolated from an urban wastewater treatment plant

Abstract: Over 18 months, enterobacteria were isolated from the raw (189 isolates) and treated (156 isolates) wastewater of a municipal treatment plant. The isolates were identified as members of the genera Escherichia (76%), Shigella (7%), Klebsiella (12%) and Acinetobacter (4%). Antimicrobial susceptibility phenotypes were determined using the agar diffusion method for the antibiotics amoxicillin, gentamicin, ciprofloxacin, sulfamethoxazole/trimethoprim, tetracycline and cephalothin, the disinfectants hydrogen peroxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
141
3
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 226 publications
(159 citation statements)
references
References 35 publications
12
141
3
3
Order By: Relevance
“…The percentage of our multiresistant E. coli harbouring integrons was lower than that reported for clinical isolates, but exceeded that recently published by Ferreira da Silva et al (2007), who detected integronspecific regions, with sizes in the range 1 -1.5 kbp or more, in 10% and 9.6% of E. coli spp. isolates from crude and treated wastewater, respectively.…”
Section: Resultscontrasting
confidence: 43%
See 1 more Smart Citation
“…The percentage of our multiresistant E. coli harbouring integrons was lower than that reported for clinical isolates, but exceeded that recently published by Ferreira da Silva et al (2007), who detected integronspecific regions, with sizes in the range 1 -1.5 kbp or more, in 10% and 9.6% of E. coli spp. isolates from crude and treated wastewater, respectively.…”
Section: Resultscontrasting
confidence: 43%
“…Experimental studies have shown that enteric pathogens can become antibiotic resistant by acquiring conjugative R plasmids from E. coli in the intestine (Poppe et al 2005). However, there are relatively few available data on the prevalence of conjugative R plasmids and integrons in E. coli in wastewater used for irrigation (Ferreira da Silva et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Although more than 90% of integrons were eliminated, the normalized copy number of class 1 and class 2 integrons was not reduced, and around 10 16 integrons were released each day into environmental water ( Figure 5). It has previously been shown that activated sludge processes, which reduce total bacterial loads, do not specifically eliminate bacteria harboring integrons (Ferreira da Silva et al, 2007;Zhang et al, 2009a). Nevertheless, we found that the WWTP reduced the diversity of gene cassette arrays contained in the raw wastewater, underlining the effect of the biological treatment on the anthropogenic integron pool arriving at the WWTP.…”
Section: Hospital Effluent Impact On Integron Dissemination T Staldercontrasting
confidence: 32%
“…isolates was also observed in the treated effluent in comparison with the raw wastewater. 33,34 Rizzo et al also found that E. coli population of mutation could survive the disinfection process. 26 Multiple antibiotic resistant bacteria can disseminate antibiotic resistance determinants to susceptible strains of the same species or to other species or genera by different mechanisms, mainly by plasmids.…”
Section: Discussionmentioning
confidence: 99%